Transit timing at Torun Center for Astronomy - Bykowski, W.; Maciejewski, G. (Advances in Astronomy and Space Physics, 2011)
The transit monitoring is one of well-known methods for discovering and observing new extrasolar planets. Among various advantages, this way of searching other worlds does not require complex and expensive equipment - it can be performed with a relatively small telescope and high-quality CCD camera. At the Center for Astronomy of Nicolaus Copernicus University in Toru«, Poland, we collect observational data using the 60-cm Cassegrain telescope hoping that it would be possible to discover new objects in already known planetary systems using the transit timing variation method. Our observations are a part of a biggercooperation between observatories from many countries.